Price, income and nutrition course: Tufts University and IFPRI course - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
This class introduces basic micro- and macro-economic concepts important to food policy. The 19 sessions that will run 135 minutes each will place emphasis on understanding alternative economic policies, and how and why they can affect food consumption and nutrition. Current research and work in progress (mostly by IFPRI colleagues) will illustrate many of the concepts discussed in class, as well as classic" readings in food policy. Topics: Overview of the role of incomes and prices in determining nutritional status/; Policy approaches to incomes and prices as mechanisms for affecting food consumption/; Methods for evaluating effectiveness of price and income policies (overview)/; Effectiveness of price and income policies/; Basic economic concepts: Supply, demand, equilibrium, price formation, and elasticity/; Basic economic concepts: Household consumption, utility analysis, indifference curve analysis, income and substitution effects, normal and inferior foods, and income-specific consumption parameters/; Extensions: Demand for micronutrients; effects of intrahousehold distribution on elasticity estimates, time allocation, and demand for food/; Farm household behavior and price policy: Production functions, marketed surplus, and prices as determinants of income and consumption of farmers and non-farmers/; Markets: Functions and failures/; Extensions: Nutrition and farm productivity, gender and agricultural production, and agricultural supply and nutrition/; Consumer price interventions: Explicit subsidies to consumers, implicit subsidies to consumers, subsidies to producers, effectiveness, and implementation issues/; Income interventions: Types, effectiveness, and differences between LDCs and developed safety net and food for work programs/; Intrahousehold issues: alternative views of the household, evidence on intrahousehold allocation, household composition and individual consumption, differential control of assets and incomes within the household/; Policy analysis case study/; Macro food policy: Macro prices and food sector, rural-urban terms of trade, and issues of urban bias/; Structural adjustment"